Analisa Komparatif Kinerja Keuangan Sebelum dan Sesudah Merger atau Akuisisi Perusahaan di Indonesia - Listiana Laelisakdiyah, Ana; Oktafiyani, Melati; Dapit Pamungkas, Imang; Kinasih, Hayu Wikan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze and compare the financial performance of Indonesian companies before and after a merger and acquisition (M&A) event, using a comparative descriptive quantitative approach. The research population includes companies listed on the Indonesia Stock Exchange, with a sample of 36 public companies that underwent M&A between 2021 and 2023. Financial performance is measured using four key financial ratios, namely Liquidity (Current Ratio), Solvability (Debt to Equity Ratio), Activity (Total Asset Turnover), and Profitability (Return On Assets). Due to non-normal data distribution, the Wilcoxon Signed Ranks Test was used for hypothesis testing. The results indicate that the Current Ratio (CR), Total Asset Turnover(TATO), and Return on Assets (ROA) showed no significant difference before and after M&A, suggesting that liquidity, operational efficiency, and profitability remained relatively stable post-consolidation. Conversely, the Debt to Equity Ratio (DER) showed a significant difference, indicating a notable change in the company’s capital structure after the M&A event, possibly due to adjustments in funding composition like increased debt or equity restructuring. Overall, M&A has not fully managed to enhance short-term efficiency and profitability, but it significantly impacts the capital structure and contributes to long-term financial stability.